Vitamin D intake as well as circulating 25-hydroxyvitamin D level and risk for the incidence and recurrence of colorectal cancer precursors: A meta-analysis - Guo, Li-liangzi; Chen, Si-si; Zhong, Li-xian; He, Kai-yin; Li, Yu-ting; Chen, Wei-wei; Zeng, Qiu-ting; Tang, Shao-hui (Frontiers in Medicine, 2022)
Objective: Vitamin D consumption and circulating 25(OH)D level are associated with decreased risk of colorectal cancer (CRC) and colorectal adenoma (CRA), but few studies have assessed their relationship with the incidence and recurrence of CRC precursors. Therefore, we performed this meta-analysis to further evaluate the association. Methods: We searched PubMed, Web of Science, Scopus and Embase databases in English until August 2021. Studies evaluating the association of vitamin D intake and circulating 25(OH)D level with risk of CRC precursors were included. A random-effects model was used to pool the risk estimates. Results: A total of 48 studies were selected for inclusion. The CRC precursors incidence was negatively correlated with total vitamin D intake (RR=0.84 95%CI: 0.80-0.88) and circulating 25(OH)D level (RR=0.79 95%CI: 0.67-0.92). However, vitamin D intake and circulating 25(OH)D level did not show significant effects on the risk of CRC precursors recurrence. For dose-response analysis, evidence of a linear association was found between CRC precursors incidence and circulating 25(OH)D level, and the risk decreased by 14% per 10ng/ml increment of circulating 25(OH)D level (RR=0.86 95% CI: 0.75-0.99). Conclusions: Vitamin D intake and circulating 25(OH)D level can play an effective role in reducing the risk of incidence of CRC precursors. However, they have not prevented the recurrence of CRC precursors.